Microfacies and Digenesis Processes of Yamama Formation in West Qurna oilfield, South of Iraq - Abd, Mona Anad (Journal of natural sciences, life and applied sciences, 2020)
Yamamma Formation is considered as the second biggest oil reservoir in southern Iraq. In this study the data was collected from seven oil wells in West Qurna oilfield (WQ- 12، WQ- 14، WQ- 15، WQ- 60، WQ- 115، WQ- 148، WQ- 215)، these wells are distributed on the crest and the flanks of the structure، and 240 thin section slides were prepared and examined after setting up the upper and lower limits of Yamamma Formation، results of the microscopic examination indicated that there are six facies represent the sedimentary environment of Yamamma Formation that formed in the variable environment such as shallow lagoon، shoal and fore- slope. Microscopic examination also showed that the formation was affected by many diagenesis processes، mostly cementation associated with dissolution other important diagenesis are micritization، compaction and dolomitization that affected the porosity system of Yamamma Formation and led to development or degradation of porosity in different ratios vertically and laterally.
Keywords: formation of the dove; facies; modulatory processes